An application of the dual identity model and active categorization to increase intercultural closeness - Prasch, Johanna E.; Neelim, Ananta; Carbon, Claus-Christian; Schoormans, Jan P. L.; Blijlevens, Janneke (Frontiers in Psychology, 2022)
The enhancement of social inclusion is a key to maintaining cohesion in society and to foster the benefits of cultural diversity. Using insights from the Dual Identity Model (DIM) with a special focus on active categorization, we develop an intervention to increase social inclusion. Our intervention encourages the participants to (re-)categorize on a superordinate level (i.e., a human identity) while being exposed to their own culture. Across a set of experiments, we test the efficacy of our intervention against control conditions on the effect of social inclusion, measured by perceived social distance. Results show an increase in cultural closeness and provide preliminary support for the use of a DIM-based intervention to increase intercultural inclusion